2011
DOI: 10.1007/s10681-011-0445-7
|View full text |Cite
|
Sign up to set email alerts
|

Allele mining and haplotype discovery in barley candidate genes for drought tolerance

Abstract: In the present study, allele mining was conducted on a panel of drought related candidate genes in a set of 96 barley genotypes using EcoTILL-ING, which is a variant of the targeting induced local lesions in genomes (TILLING) technology. Analyzing approximately 1.5 million basepairs in barley a total number of 94 verified unique haplotypes were identified in 18 amplicons designed for 9 genes. Overall, 185 single nucleotide polymorphisms (SNPs) and 46 insertions/deletions (INDELs) were detected with a mean of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 57 publications
1
10
1
Order By: Relevance
“…Compared to previous reports on barley [36], [38], nucleotide diversity (π = 0.00118) of HSP17.8 was lower, and the level of haplotype diversity (0.526) was higher in this study. The average frequency of SNPs was 1 per 54.5 bp, which was similar to that found in Chen et al (1 SNP/53.8 bp) [39], lower than Zeng et al(1 SNP/9.8 bp) [40], and higher than Rostoks et al (1 SNP/200 bp) [41].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Compared to previous reports on barley [36], [38], nucleotide diversity (π = 0.00118) of HSP17.8 was lower, and the level of haplotype diversity (0.526) was higher in this study. The average frequency of SNPs was 1 per 54.5 bp, which was similar to that found in Chen et al (1 SNP/53.8 bp) [39], lower than Zeng et al(1 SNP/9.8 bp) [40], and higher than Rostoks et al (1 SNP/200 bp) [41].…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, Tajima's D neutrality test revealed no evidence of natural selection for HSP17.8 (Table 4) but under some kind of purifying selection as revealed by a high negative value of Tajima's D. This insignificant result may be attributed to the low number of SNPs observed, which weakens the neutrality test. This result agrees with previous reports on other functional genes in barley [36] and CPsHSP-2 in Machilus kusano [37]. However, the Tajima's D value in Africa was positive, which may result from balancing selection or bottleneck effect.…”
Section: Discussionsupporting
confidence: 91%
“…ulations (Du et al, 2004;Cseri et al, 2011). Under both salinity and drought stress, transgenic HVA1 mulberry plants showed improved cellular membrane stability (CMS), higher photosynthetic yield, less photo-oxidative damage, and better water use efficiency compared to the non-transgenic plants (Lal et al, 2008).…”
Section: A B Cmentioning
confidence: 99%
“…Based on overlapping haplotype sequences, markers were developed for four candidate genes: HvARH1 , HvSRG6 , HvDRF1 and HVA1, which distinguished between the tolerant and susceptible cultivars (Cseri et al. ).…”
Section: Generation Of Mutants With Novel Genetic Variationmentioning
confidence: 99%
“…Overall, 185 SNPs and 46 Indels were discovered and found to be associated with drought tolerance. Based on overlapping haplotype sequences, markers were developed for four candidate genes: HvARH1, HvSRG6, HvDRF1 and HVA1, which distinguished between the tolerant and susceptible cultivars (Cseri et al 2011).…”
Section: Generation Of Mutants With Novel Genetic Variationmentioning
confidence: 99%